HEDGING DAN PERKEMBANGANNYA - Husni Husni (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2018)
Hedging transactions are transactions that have been widely used, both in the financial sector and in other fields. However, this transaction is not too familiar to many people. This paper briefly presents the understanding, history, instruments and advantages and disadvantages of hedging. Keywords: Hedging, Risk, Exchange Rate, Price